Effect of Different Disinfection Methods on Quality of Tap Water - Jachimowski, Artur (Geomatics and Environmental Engineering, 2019)
This paper specifies the effect of using strong oxidants in water treatment technologies on the formation of disinfection by-products. The study was developed by collecting water samples from four water treatment plants of the Municipal Water and Sewerage Company (MPWiK) in Krakow and at selected sampling points within the water supply networks. The analysis was comprised of selected indicators of water quality after the treatment process during the years of 2011‑2017. From the carried-out investigation, it was concluded that the concentration of free chlorine in the water supply network concurrently decreased with increases in the distance from the treatment plant. This dependence was found in 19 out of 28 water supply points. While analyzing the annual average concentrations of free chlorine in the municipal water, it was noted that the highest values at the study points occurred in 2011. During the other years, decreases in this indicator were observed. This follows from the analysis that the water disinfection by-products did not exceed permissible limits.